Acts - Bock, Darrell L.; Yarbrough, Robert W.; Stein, Robert H. (Grand Rapids, Mich. : Baker Academic, 2007)
Following his authoritative two-volume commentary on Luke in the acclaimed BECNT series, Darrell Bock now provides a substantive yet highly accessible commentary on Acts in this latest addition to the series. With extensive research and thoughtful chapter-by-chapter exegesis, Bock leads readers through all aspects of the book of Acts--sociological, historical, and theological--to help them better understand and explain this key New Testament book. As with all BECNT volumes, Acts features the author's detailed interaction with the Greek text. This commentary admirably achieves the dual aims of the series--academic sophistication with pastoral sensitivity and accessibility--making it a useful tool for students, professors, and pastors. The user-friendly design includes shaded-text chapter introductions summarizing the key themes of each thought unit. - Publisher.
Introduction: Jesus ascends to the Father and gives a mission (1:1-11) -- The early church in Jerusalem (1:12-6:7) -- Persecution in Jerusalem moves the message to Judea and Samaria as a new witness emerges (6:8-9:31) -- The Gospel to the Gentiles and more persecution in Jerusalem (9:32-12:25) -- The mission from Antioch and the full incorporation of Gentiles (13:1-15:35) -- The second and third missionary journeys : expansion to Greece and consolidation amid opposition (15:36-21:16) -- The arrest : the message is defended and reaches Rome (21:17-28:31).
Includes bibliographical references (pages 761-781) and indexes.
Keywords: Bible. -- Commentaries